Computational analyses prioritize and reveal the deleterious nsSNPs in human angiotensinogen gene. (February 2020) - Goswami, Achintya Mohan
Graphical abstract: Highlights: Highly damaging and pathogenic nsSNPs in human angiotensinogen gene are predicted. Majority of deleterious nsSNPs in human angiotensinogen are evolutionary conserved. Several nsSNPs are found to affect thermodynamic stability and post-translational modifications of angiotensinogen. Various nsSNPs are found to destabilize the renin-angiotensinogen interaction. Angiotensinogen deregulation is observed to impact survival in patients with gastric and breast cancer. Abstract: Angiotensinogen (AGT) is a key component of renin-angiotensin-aldosterone system (RAAS), which plays central role in blood pressure homeostasis. Association of AGT polymorphisms have been investigated in different ethnic populations in variety of cardiovascular and non-cardiovascular conditions. In this study, 354 non-synonymous SNPs (nsSNPs) of AGT were evaluated to predict damaging and structurally important variants. Majority of the deleterious nsSNPs occurred in the evolutionary conserved regions. Several of these nsSNPs were found to affect post-translational modifications like methylation, glycosylation, phosphorylation, ubiquitination etc. Structural evaluations predicted 19 variants as destabilizing and some of them were also predicted to destabilize the renin-AGT interaction. Therefore, the present computational investigation predicted pathogenic and functionally important variants of human AGT gene. The study has also shown that AGT deregulation is associated with survival outcome in patients with gastric and breast cancer, using microarray gene expression profile. Furthermore, the computationally screened nsSNPs can be analyzed in population based genotyping studies and may help futuristic drug development in the area of AGT pharmacogenomics.